Kebijakan Ketua Yayasan dalam Meningkatkan Kesejahteraan Guru di Taman Pendidikan Al-Qur’an (Tpq) Al-Afkar, Bungurasih - Ika Khaironi; Ahmad Fakk Dominika Taqi Aha Putra; Mufidatur Rofia; Nur Ali; J. Nabiel Aha Putra (Universitas Negeri Malang, 2025)
Abstract: Departing from the problem of low teacher welfare in non-formal Islamic educational institutions, this study analyzes the policy of the head of the Al-Afkar Bungurasih Foundation in improving the welfare of teachers of the Al-Qur'an Education Center. The research uses a descriptive qualitative approach with observational data collection techniques, structured interviews, and documentation; Data analysis was carried out through reduction, presentation, and conclusion drawing with a test of the validity of triangulation techniques. The results show three main policy clusters. First, financial policy: the determination of proportional honorarium based on the number of students fostered and the facilitation of voluntary appreciation funds from student guardians distributed directly without deductions including support for momentum such as holiday allowances. Second, the professional development policy: teachers' participation in the training of the Mu'allimil Qur'an (MMQ) Council accompanied by incentives as a form of appreciation and encouragement to improve pedagogical competence. Third, participatory governance policies: monthly routine deliberation as a communication forum, honorarium evaluation, identification of obstacles, and collective decision-making. The implementation of these policies has an impact on increasing teacher motivation, discipline, and responsibility, which is reflected in the readiness of teaching materials, seriousness in learning, and activeness in evaluation; in turn contributes to the quality of Qur'an learning services at TPQ. The findings confirm that a combination of financial policy, capacity building, and participatory governance is a strategic prerequisite for the elevation of teacher welfare and the quality of Qur'anic education in the context of foundations. Keywords: Foundation policy; teacher well-being; Al-Qur’an Education Center Abstrak: Berangkat dari rendahnya kesejahteraan guru pada lembaga pendidikan Islam non-formal, penelitian ini bertujuan untuk menganalisis kebijakan Ketua Yayasan Al-Afkar Bungurasih dalam upaya meningkatkan kesejahteraan guru TPQ. Penelitian ini menggunakan pendekatan kualitatif dengan jenis studi kasus. Data dikumpulkan melalui observasi, wawancara terstruktur, dan studi dokumentasi. Selanjutnya, data dianalisis melalui proses reduksi, penyajian, dan penarikan kesimpulan, dengan validitas data diuji melalui teknik triangulasi. Hasil penelitian menunjukkan bahwa terdapat tiga kebijakan utama yang diterapkan oleh yayasan. Pertama, kebijakan keuangan, meliputi penetapan honorarium berdasarkan jumlah santri binaan, penyaluran dana apresiasi sukarela dari wali santri tanpa potongan, serta pemberian tunjangan pada momentum tertentu seperti Hari Raya. Kedua, kebijakan pengembangan profesional, yaitu mendorong guru untuk mengikuti pelatihan yang diselenggarakan oleh Majelis Mu’allimil Qur’an (MMQ), disertai pemberian insentif sebagai bentuk apresiasi dan motivasi dalam meningkatkan kompetensi pedagogik. Ketiga, kebijakan pengelolaan partisipatif, yang diwujudkan melalui pelaksanaan musyawarah rutin bulanan sebagai forum komunikasi, evaluasi honorarium, identifikasi kendala, dan pengambilan keputusan secara kolektif. Implementasi ketiga kebijakan tersebut memberikan pengaruh positif terhadap peningkatan motivasi dan tanggung jawab guru. Hal ini tercermin dari kesiapan guru dalam menyiapkan bahan ajar, kesungguhan dalam melaksanakan proses pembelajaran, serta partisipasi aktif dalam kegiatan evaluasi. Secara keseluruhan, kebijakan yang terintegrasi antara aspek finansial, profesional, dan manajerial terbukti berkontribusi signifikan terhadap peningkatan kesejahteraan guru sekaligus mutu layanan pembelajaran Al-Qur’an di TPQ Yayasan Al-Afkar Bungurasih. Kata kunci: Kebijakan yayasan; Kesejahteraan Guru, Taman Pendidikan Al-Qur’an.